2019
DOI: 10.1001/jamafacial.2018.1962
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Outcomes in Botulinum Therapy for Patients With Facial Synkinesis

Abstract: In the last decade, there has been a significant increase in the number of practitioners administering botulinum toxin for facial synkinesis. However, there are few resources available to guide treatment patterns, and little is known about how these patterns are associated with functional outcomes and quality of life.OBJECTIVE To evaluate botulinum treatment patterns, including the dosing and frequency of muscle targeting, for treatment of facial synkinesis and to quantify patient outcomes. DESIGN, SETTING, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
3
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 37 publications
6
57
3
11
Order By: Relevance
“…Several groups described an increase of BoNT dosage in patients with synkinetic defective healing and support our results 5,12,18,19 . Kollewe et al demonstrated an increase of BoNT dosage in 14% of the patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Several groups described an increase of BoNT dosage in patients with synkinetic defective healing and support our results 5,12,18,19 . Kollewe et al demonstrated an increase of BoNT dosage in 14% of the patients.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, Choi et al emphasised use of a lower dosages of OnaBoNT. There are several reports showing that higher amounts of OnaBoNT are well tolerated and are associated with higher satisfaction scores and more favourable outcome 12,20 . Amount of AboBoNT (68 units) was higher in our patients than reported elsewhere 20 .…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Regardless of its etiology, idiopathic (Bell’s Palsy) or secondary facial nerve palsy, due to multiple etiologies such as Ramsey Hunt syndrome, infection, vascular, tumor resection and base of skull injuries, among others, manifests a unilateral peripheral facial nerve palsy which may lead to involuntary static and dynamic alterations of facial expression due to aberrant regeneration of fibers in the neural repair process in as many as 55.5% of patients with longstanding facial weakness [ 1 , 2 , 3 , 4 , 5 ]. The imbalance, static and dynamic, resulting from the muscular paralysis may not only jeopardize simple daily tasks such as articulation, eating and drinking, but is often cosmetically unacceptable to patients due to asymmetry, rendering psychological consequences such as low self-esteem, social isolation, anxiety, and depression [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%